INCUBATOR Lab: Where Artists Collaborate with Life. (1st June 2019) - Willet, Jennifer
This article presents the research philosophies, artworks, and practices of INCUBATOR Lab, a bioart research and teaching facility at the School of Creative Arts, University of Windsor, Canada. Research/creation projects produced range from microbial artworks, interspecies performances, social practice projects, and textual analysis, to artworks that can only be seen with a microscope. The facility provides innovations in public engagement through (1) making daily bioart laboratory activities visible to online and local audiences; (2) serving as a gallery where artworks that are unable to leave the BSL2 laboratory setting can be safely displayed for audiences; and (3) providing a multimedia performing arts venue where seated audiences can view theatre and performance events that integrate BSL2 biotechnologies into multimedia storytelling and performance genres. INCUBATOR Lab is an institutional space, an artwork, an ecology, and a biosphere where human and non-human organisms collaboratively and co-dependently produce bioart research and creation.